Investigating the relationship of electronic health literacy and self-care behaviors with life quality in patients with heart failure - Masoomeh Bakhshayesh; Mitra Hojatansari; Soheila Rabie Siahkali (Zanjan University of Medical Sciences and Health Services, 2023)
Background: A suitable approach to improve the quality of life (QoL) of patients with heart failure (HF) is to promote electronic health literacy (e-HL) and encourage self-care behaviors among patients. Objectives: This study was conducted to divulge the association of e-HL and self-care behaviors with QoL in patients with HF. Methods: This cross-sectional descriptive study was conducted on 200 patients suffering from HF admitted to the CCU and POST-CCU departments of the Amir-Al Momenin Hospital of Maragheh City, Iran, who were enrolled by convenience sampling. Data were collected using WHO Quality of Life-BREF (WHOQOL-BREF), the e Health Literacy Scale (e HEALS), and the European Heart Failure Self-care Behavior Scale (EHFScBs) and analyzed using SPSS v. 21 Software. The statistical tests included ANOVA, the independent t-test, Pearson correlation, and hierarchical linear regression. Results: The Pearson correlation test showed that there was a direct and statistically significant relationship between e HL, self-care behaviors, and QoL (P-value <0.05). The correlation between self-care behaviors and QoL was the strongest (r=0.747, P-value <0.001). According to hierarchical linear regression analysis, self-care behaviors were the strongest predictors of QoL (β =0.647, P-value =0.001). Overall, e-HL (β=0.163, P-value=0.001), self-care behaviors (β=0.647, P-value <0.001), and demographic variables were able to predict 57.6% of the variance of QoL (R=0.576, P-value <0.001). Conclusion: Electronic health literacy and self-care behaviors may play an important role in improving the QoL of HF patients. Regarding the role of these parameters in preventing and managing HF, the health system should pay attention to upgrading these elements by appropriate training.